Neglected Fournier’s Gangrene Caused by Acinetobacter baumannii: A Rare Case Report - Arif Emre; Mehmet Sertkaya; Sami Akbulut; Yakup Duman; Ilhami Taner Kale (Case Reports in Surgery)
Fournier’s gangrene, rare but life threatening disease, is characterized by an acute necrotic infection of the scrotum, penis, or perineum. Fournier’s gangrene is a mixed infection caused by both aerobic and anaerobic bacteria. Fournier’s gangrene caused by multidrug resistant Acinetobacter baumannii have been reported rarely. The mainstay of treatment is prompt recognition and a combination of antibiotics with radical debridement. We describe a case of a 56-year-old male patient presenting with neglected Fournier’s gangrene caused by Acinetobacter baumannii. Many treatment modalities including broad-spectrum antibiotics, aggressive debridement, negative pressure wound therapy, diversion colostomy, and partial-thickness skin grafts were applied to save the patient’s life.